Marriage and conjugal sex "marriage dept" and Kant's "conjugal rights" - Calano, Mark Joseph T. (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2016)
The code of canon law states that sex is a requisite for the consummation of a marriage but that conjugal act must be performed in a "human way." Divided into three parts, this paper investigates the place of human sex in a consummated marriage by looking into the Pauline understanding of the "marriage dept" found in 1 Corinthians 7 and the Kantian notion of "conjugal rights." The first part is an exegesis of Paul's texts suggesting that a couple are obligated by a certain dept to provide for the sexual gratification of their partners. The second part discusses implications of the Kantian principle of humanity in marriage and sexual activity. For Kant, marriage is a contact that includes the exchange of rights of access to the body. By explicating Paul's and Kant's understanding of the relationship between marriage and sex, the paper provides a better understanding of the place and role of human sex in a consummated marriage.